2010
DOI: 10.1097/icl.0b013e3181d0b604
|View full text |Cite
|
Sign up to set email alerts
|

The Orbscan Acoustic (Correction) Factor for Central Corneal Thickness Measures of Normal Human Corneas

Abstract: Orbscan pachymetry can be expected to yield CCT data that is approximately 7% higher than U/S. The global application of a 0.92 AF does not robustly align the Orbscan CCT data to that of U/S and, in fact, can easily result in the data being as much as 7% lower. Overall, the level of agreement between Orbscan and U/S is limited, and Orbscan data should simply be reported as measured without any adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Doughty and Jonuscheit18 performed a meta-analysis of 46 studies evaluating Orbscan measurements with and without the correction factor; results showed that Orbscan may yield CCT measurement which is approximately 7% higher than US pachymetry. Some studies have suggested that universal use of correction factor of 0.92 may be inaccurate, and CCT measurements with Orbscan should be reported without any adjustment factor 1315,18. This discrepancy between studies may be due to the fact that Orbscan measures thickness between air-tear interface and posterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Doughty and Jonuscheit18 performed a meta-analysis of 46 studies evaluating Orbscan measurements with and without the correction factor; results showed that Orbscan may yield CCT measurement which is approximately 7% higher than US pachymetry. Some studies have suggested that universal use of correction factor of 0.92 may be inaccurate, and CCT measurements with Orbscan should be reported without any adjustment factor 1315,18. This discrepancy between studies may be due to the fact that Orbscan measures thickness between air-tear interface and posterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…The CCT may decrease with increasing age [25], and female sex has also been associated with lower CCT [17]. The Orbscan system may overestimate CCT value as compared to the ultrasound pachymeter [22].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, AFs minimize the mean difference between two methods,[11] but for the extremes of CCT this may lead to over or under estimation (which represents the effect of absolute CCT on degree of inter-device agreement). Indeed, correcting CCT readings in the thin range of CCT with a correction factor which is appropriate for thicker corneas would lead to underestimations.…”
Section: Introductionmentioning
confidence: 83%
“…This logical deduction was supported by our observation in this study as well as previous reports. In a review of 47 studies, Doughty and Joncheit [11] concluded “the global application of a 0.92 AF does not robustly align the Orbscan CCT data to that of the US pachymetry and; in fact, can easily result in the data being as much as 7% lower.”…”
Section: Discussionmentioning
confidence: 99%